Mobile Augmented Reality Untuk Pembelajaran IPA Kelas 7 Kurikulum 2013 - Dwi Susanto; Achmad Basuki; Doni Rahman Hakim (SENTIA 2016, 2016)
Rapid technological developments also affects education, especially if the technology is combined with the proper pedagogic. The combination of both can improve the quality of learning and can bring a new learning experience. One of the technologies developed at this time is the Augmented Reality (AR) which can be used as a new means of learning. In the 2013 curriculum, science textbooks for grade 7 are arranged thematically, and students are expected to search of learning resources available around them. Augmented Reality applications based on mobile was created as a support technology when the process of learning science is happening by using science textbooks Grade 7 curriculum 2013 of Chapter I. From the test results obtained, this application can help students understand the material in Chapter I.